THE The Influence Of School Organizational Climate And Work Motivation On The Professional Competence Of Elementary School Teachers - Dewi, Endah Kurnia Sinta; Yuliejantiningsih, Yovitha; Haryati, Titik (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
This study examines school organizational climate and work motivation effects on elementary teachers' professional competence in Jambu Subdistrict, Semarang Regency's 18 rural schools. Previous studies found moderate correlations (Dharmawaty et al., 2022: r = 0.45; Sumantri & Whardani, 2017: R² = 0.28), but simultaneous examination in rural contexts remains limited. Using ex post facto design, 125 teachers were surveyed through proportional random sampling. Instruments measured professional competence (content mastery, student understanding, curriculum application), organizational climate (learning quality, inclusivity, learning culture), and work motivation (internal/external factors) with validated items like